Pariwisata Dan Pelestarian Warisan Budaya - nfn. Siswanto (Balai Arkeologi Yogyakarta, 2007)
The development paradigm in many countries is now more oriented towards the development of the service sector and industry, including the tourism industry. Likewise in Indonesia in the last three decades the tourism sector has been encouraged and responded positively by the government with the hope of replacing the oil and gas sector which has been the prima donna in the country's foreign exchange earnings. The tourism sector is promising enough to help increase foreign exchange reserves and also pragmatically to increase people's income. The national situation is now beginning to show progress towards stability, especially in the political and security fields will provide assurance of confidence for foreign tourists to enter Indonesian territory.